Students’ Perception on The Use of Google Classroom in The Online and Onsite Learning Mode - Diantari, Ayu Melani; Artini, Luh Putu; Dewi, Kadek Sintya (English Education Department STKIP Agama Hindu Singaraja, 2023)
This article’s objective was to investigate students’ perception on the use of google classroom in the online and onsite learning mode during the transition period of pandemic education. The research was a descriptive study that uses qualitative methods. The study was conducted at a public school at South-Bali, Indonesia; with the subject of approximately 80 students. The data collection process was done through survey and interview employing questionnaire and interview guide. Instruments were validated through content validation conducted through expert judges. There were five factors that were used to measure the students’ perception on the use of Google Classroom in the online and onsite learning, namely: ease of access, sense of usefulness (perceived usefulness), communication and interaction, presentation of instructional materials (perceived instruction delivery), and satisfaction. The data from were analyzed using several steps proposed, including quantified data analysis and interactive model such as data collection, data reduction, data display, and conclusion drawing. Results portrayed that the investigated students had positive perception towards the use of Google Classroom in EFL online learning context and in EFL onsite learning context. Results also portrayed that the score of the students’ perception in onsite learning was higher, or in other word, was more positive than the online learning in the use of Google Classroom. The students positively perceived the use of Google Classroom in the current face-to-face meeting as a platform for sharing and accessing learning materials and organizing assignment.